PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN VIDEO TERHADAP HASIL BELAJAR SISWA SMPN 8 PONTIANAK - Hasanah, Nurul; Marlina, Reni; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to determine the effect of the Problem-Based Learning Model using video on students? learning outcomes on the material of environmental pollution. It was an experimental study on seventh-grade students of SMAN 8 Pontianak. The research was conducted in the form of a Quasi-Experimental Design using a Nonequivalent Control Group Design. The sample was selected using an intact group technique, of which class VII D engaged in the experimental group and VII B in the control group. The instrument applied for collecting the data was in the form of 20 items of the multiple-choice test. Based on the analysis, the experimental group instructed using the applied learning model resulted in higher mean scores by 16.04 than the control group by 13.54. The result of the U Mann-Whitney test shows Zcount is smaller than -Ztable (-2.66 < -1.96). It shows that there is a difference between the learning outcomes of students taught using the selected learning model and those taught using a conventional way. The effect size on a high category by 0.80 shows that the problem-based learning model using video affects the students? learning outcomes by 28.81%. Keywords: Learning Outcomes, Problem Based Learning